Fluorescence lifetime optical projection tomography and FRET applied to visualizing apoptosis in live zebrafish larvae - Andrews,N; Ramel,MC; Kumar,S; Alexandrov,Y; Kelly,DJ; Warren,SC; Kerry,L; Lockwood,N; Frolov,A; Frankel,P; Bugeon,L; McGinty,J; et al. (2016)
We present the application of FLIM-OPT to read out biological function in live transgenic zebrafish larvae using a genetically expressed cleavable FRET biosensor for Caspase-3 as an indicator of gamma radiation induced apoptosis.